Pesantren di Bengkulu : Sejarah dan Perkembangannya - Moch. Iqbal (Universitas Islam Negeri Fatmawati Sukarno, 2023)
The purpose of this paper is to examine the growth and development of Islamic Boarding Schools in Bengkulu. This study is important considering its very rapid development and high public response, especially at the beginning of the 21st century. Using library research methods, namely by researching available literature, related to relevant themes. Both off-line and on-line sources are widely available. The results of the study reveal that first, Islamic education in Bengkulu started from the school model pioneered by the Islamic modernist movement Muhammadiyah and other Islamic organizations from pre-independence until the end of the 20th century. Second, pesantren is a relatively new phenomenon, compared to the history of the birth and development of Islamic boarding schools in Indonesia. Third, the first Islamic boarding school that was established in Bengkulu was precisely at the initiative of President Soeharto who wanted Bengkulu to have an institution such as a pesantren, so that the Pancasila pesantren was born in 1973. Third, starting in the 2000s, pesantren emerged in the Bengkulu City area and its surroundings with a modernist style. Tujuan dari penulisan ini adalah untuk mengkaji tumbuh dan berkembangnya Pondok Pesantren di Bengkulu. Kajian ini penting mengingat perkembanganya yang sangat pesat dan respon masyarakat tinggi, terutama pada awal abad 21. Menggunakan metode penelitian pustaka, yaitu dengan meneliti literature yang tersedia, terkait dengan tema yang relevan. Baik sumber yang bersifat off-line maupun sumber on-line yang banyak tersedia. Hasil penelitain mengungkapkan bahwa pertama, pendidikan Islam di Bengkulu diawali dari model sekolah yang dipelopori oleh gerakan modernis Islam Muhammadiyah dan ormas islam lainnya sejak pra-kemerdekaan hingga akhir abad 20. Kedua, pesantren adalah fenomena relative baru, dibanding sejarah lahir dan berkembangnya pesantren di Indonesia. Ketiga, Pesantren pertama yang berdiri di Bengkulu justru atas inisiatif presiden Soeharto yang menginginkan Bengkulu mempunyai lembaga semacam pesantren, sehingga lahirlah pesantren Pancasila pada tahun 1973. Ketiga, mulai tahun 2000an, pesantren bermunculan di wilayah Kota Bengkulu dan sekitarnya dengan corak modernis.